Pendampingan Pencegahan Penularan Covid-19 Melalui Penyuluhan Kesehatan Dan Pembuatan Hand Sanitizer Di Lingkungan Asrama Panti - Nurhayati Nurhayati; Oktarianita Oktarianita; Ferasinta Ferasinta (Jurnal Pengabdian UntukMu NegeRI, 2022)
The world has now been impacted by COVID-19. Indonesia has recently become one of the countries that have been affected by COVID-19 with the highest number of COVID-19 cases in Asia. As the incidence of COVID-19 increases rapidly, it is necessary to prevent the transmission of COVID-19 especially in a populous area or dorm area. This community service was implemented by lecturers and nursing students of the Department of Nursing, Muhammadiyah Bengkulu University. Some programs included a health education of COVID-19 which is manifested in training activities for making natural hand sanitizer derived from betel leaf and lime. This program has now been implemented by students in Panti Sosial Bina Netra of Bengkulu.